How perspectives on food safety of vendors and consumers translate into food choice behaviors in six African and Asian countries - Isanovic, S.; Constantinides, S.V.; Frongillo, Edward A.; Bhandari, S.; Samin, S.; Kenney, E.; Wertheim-Heck, Sigrid C.O.; Nordhagen, S.; Holdsworth, M.; Domínguez-Salas, Paula; Ambikapathi, R.; Laar, A.; et al. (Elsevier, 2023)
Background Consumption of unsafe foods increases morbidity and mortality and is currently an issue, particularly in low- and middle-income countries. Policy actions to ensure food safety are dominated by mitigation of biological and chemical hazards through supply-side risk management, lessening the degree to which consumer perspectives of food safety are considered.